A study of the effect of the transfer of autonomy on motivation on physical education classes - J. A. Moreno; A. Gómez; E. Cervelló (Asociación Española de Ciencias del Deporte, 2010)
ABSTRACT The objective of this study was to test the hierarchical model of motivation of Vallerand, using and experimental approximation. Sixty eight adolescents with ages between 14 and 16 years participated in the study. Two classes were assigned to a control (no choice) group (n = 33) and other two to an experimental (choice) group (n = 35). The intervention program was a didactic unit of six meetings with pre-test and post-test. Measures of contextual and situational self-determined motivation were employed. Results show that the experimental group showed higher post-intervention values in perception of autonomy, situational and contextual self-determined motivation. The implications related to the possibility of choosing the tasks to increase the perception of autonomy and the self-determined motivation in the physical education classes were discussed in the manuscript. Key Words:Self-determined motivation, physical education, autonomy, motivational climate